Encyclopedia of chromatography - Cazes, Jack (Marcel Dekker, 2004)
In step with novel technologies and methodologies that have reshaped chromatography in recent years, this supplement reviews developments in HPLC, TLC, SFC, CCC, and other areas-presenting 50 authoritative entries filled with practical information vital to applications from biotechnology to environmental science to clinical pathology.